Recovery of phenolic compounds from the by-products of yellow mustard protein isolation. (January 2019) - Sinichi, Sayeh; Siañez, Ana Victoria Legorreta; Diosady, Levente L.
Abstract: Nanofiltration (NF) (MWCO 150–300 Da) was evaluated for the recovery of phenolic compounds from the wastewater from the production of yellow mustard protein isolates. Rejection coefficients of 0.70 and 0.87 and transmembrane fluxes of 51.3 L/hm 2 and 28.8 L/hm 2 were observed under alkaline and acidic conditions, respectively. At low pH, 77% of the phenolic compounds fed to the process were recovered in the retentate. Combination of diafiltration (DF) with NF was beneficial only when processing at low pH. The permeate from the NF process a contained <100 ppm total phenolics, which suggests the possibility of recycling these effluents in the production of yellow mustard protein isolates. p-Hydroxybenzoic acid was the major phenolic compound found both in the waste effluent and in the products of NF processing. Sinapic acid constituted a secondary fraction, and derivatives of quercetin and kaempferol were also detected. Graphical abstract: Unlabelled Image Highlights: Nanofiltration of the by-product generated during the production of yellow mustard protein isolates enables the concentration and recovery of phenolic compounds. pH affects NF processing of the waste effluent. Under acidic conditions, 77% of the phenolic compounds in the feed solution were recovered in the retentate. Diafiltration was beneficial when NF was conducted at low pH, increasing by 10.2% the phenolic content of the dried retentate.